Corporate governance in state-owned enterprises - Mbele, Nimrod Oupa (My University, 2016)
Following a plethora of scandals in both the public and private sectors, corporate governance has become the subject of contentious debates in the public domain over the past decade As a result, codes of good practice in the form of Cadbury, Greenbury, Turnbul, Hempel, Higgs, Sarbanes-Oxley Act (SOX) and Bosch Commission were ushered in different parts of Europe, Australia and the United States of America (USA). In South Africa, the King Commission on Corporate Governance was developed and subsequently modified for State Owned Enterprises (SOEs). Despite the progress noted, the SOEs environment remains in distress as boards and management struggle to maintain a balance between legislative compliance and performance. It is in the latter context that the study was inspired by the boards of the South African Broadcasting Corporation (SABC) and the Electricity Supply Commission (Eskom) respectively struggle to actualise sound corporate governance practices in order to deliver shareholder value. As part of the qualitative research approach, primary data collection was conducted by means of comprehensive face-to-face interviews with board members and senior management at the two above-mentioned organisations. In total, 30 (thirty) board members and senior managers were interviewed. In addition, secondary data was collected in the form of records, strategy reports, business plans, and memos written to participants. In analysing qualitative interview data, the study utilised content analysis and cross-case analysis methods, on whose basis five themes were derived, namely: legislation and regulations; the interface between board and management; the role of the board in strategy development; performance monitoring of the board; as well as the organisational funding model. The findings of the study include: fragmented and convoluted legislation; blurring of lines between management and governance; a weak board performance monitoring culture; unclear prioritization of social policy agenda, and inadequate funding to support social policy programmes, such as infrastructure. The policy reviews create leadership instability and accentuate distrust between boards and senior managers. This study further emphasizes limitations of the theoretical frameworks underpinning corporate governance in SOEs, and also advances detailed understanding of the corporate governance issues facing SOEs. Key Words: State Owned Enterprises; Corporate Governance; Legislation; Regulations; Compliance; Boards; Performance, Monitoring and Evaluation.
SUBMITTED IN ACCORDANCE WITH THE REQUIREMENT FOR DEGREE OF DOCTOR OF PHILOSOPHY IN THE SUBJECT OF CORPORATE GOVERNANCE WITS SCHOOL OF GOVERNANCE FACULTY OF LAW, COMMERCE AND MANAGEMENT AT THE UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG AUGUST 2015
Keywords: Corporate governance--South Africa; Government business enterprises--South Africa; Corporations, Government--South Africa